Equilibrium Comparison Shopping - Wilde, Louis L.; Schwartz, Alan (Review of Economic Studies, 1979)
Louis L. Wilde, Alan Schwartz; Equilibrium Comparison Shopping, The Review of Economic Studies, Volume 46, Issue 3, 1 July 1979, Pages 543–553, https://doi